Research of the Dyeing Properties of Lychee Leaves and Sappan Wood Extract on Silk-Linen Fabric - Qian Lyu; Krisada Daoruang; Atiyot Sankaburanurak; Chalisa Apiwathnasorn (Textile & Leather Review, 2024)
Synthetic dyes are the primary colouring materials for textile dyeing; however, the residual industrial wastewater from the dyeing process contains complex concentrations of chemical substances, which result in toxicity and environmental pollution with severe negative impacts on ecology and health. This study adopts an eco-friendly perspective, utilizing a mixture of lychee leaves and sappan wood extracts for dyeing silk-linen fabrics. It explores the impacts of dyeing time, mordants, and dyeing methods on the colour quality of the samples. A computer colourimeter was used to compare the colour effects of different dye solution ratios on silk-linen fabrics, and the colour fastness to water, perspiration, and dry rubbing of the dyed fabrics was tested. The results show that the optimized dyeing process for silk-linen fabrics using a mixed solution of lychee leaves and sappan wood includes the following findings: Dyeing time has no significant impact on the CLE L*, a*, and b* values. The highest L* value and colour brightness are achieved under conditions without mordants. By mixing dye solutions in different proportions and treating them with mordants, the colour gamut of silk-linen fabrics has been expanded. The dyed colours are similar to the main popular colours of 2024, making them the trend colours of this year; the samples' fastness performance tests indicate that the colour fastness to water, perspiration, and dry rubbing essentially meets the requirements for textile fabrics. The use of lychee leaves and sappan wood for fabric dyeing is not only environmentally friendly but also possesses significant health-beneficial properties, offering potential commercial value.